An Analysis of Arabic Language Teaching Materials for Grade VIII at Darussalam Islamic Junior High School Pasaman Barat: تحليل المواد الدراسية في اللغة العربية للصف الثامن في المدرسة المتوسطة الإسلامية دار السلام بسامان الغربية - Resta, Winda; Wahyuni, Wira (Ukazh : Journal of Arabic Studies, 2025)
This study aims to analyze the alignment of the Arabic language instructional materials for eighth-grade students at Darussalam Islamic Junior High School Pasaman Barat with the curriculum standards outlined in the Decrees of the Minister of Religious Affairs No. 183 and 184 of 2019. These decrees serve as the primary guidelines for implementing the Islamic Religious Education and Arabic Language curriculum, emphasizing holistic competencies and higher-order thinking skills (HOTS). The researcher employed a qualitative approach using content analysis methods. The primary data consisted of the Arabic textbook used at the school, while secondary data were drawn from the official KMA documents. The findings reveal that the teaching materials are generally aligned with the thematic content mandated by the decrees. However, several shortcomings were identified, including the lack of explicit integration of spiritual (Core Competency 1) and social (Core Competency 2) aspects, an imbalanced presentation of the four language skills (listening, speaking, and writing in particular), and an overreliance on LOTS (Lower Order Thinking Skills) in assessment tasks. The study recommends revising and enhancing the teaching materials to better meet the curriculum requirements and students’ learning needs in a comprehensive and modern educational context.